Antidepressants differentially affect expression of complexin I and II RNA in rat hippocampus - Zink, Mathias; Britsch, Simone; Gebicke-Härter, Peter J.; Henn, Fritz A.; Thome, Johannes (Psychopharmacology, 2005)
Disturbance of synaptic transmission is currently viewed as an important pathophysiological mechanism and therapeutic target of mood disorders. Amongst other lines of evidence this theory is based on human post-mortem investigations showing differential expression of complexins. In order to discriminate between molecular correlates of the disease itself and effects of psychotropic drugs given to patients, we performed an animal trial using subchronic antidepressant treatment. Cohorts of adult male Sprague-Dawley rats were treated over a period of 14 days with intraperitoneal injections of either saline (0.9%, n=8), desipramine (15 mg/kg, n=7), fluoxetine (10 mg/kg, n=8), or tranylcypromine (10 mg/kg, n=5). Brain slices were used for in situ hybridizations with 35S labelled RNA probes of the genes complexin I, complexin II and syntaxin 1 A, the SNARE complex protein interacting with the complexins, and assessed semi-quantitatively for region-specific expression levels. Expression of complexin I was induced only in habenular nuclei after treatment with fluoxetine. In contrast, complexin II was significantly induced by desipramine and tranylcypromine, but not fluoxetine, in several brain regions. All treatment groups, but most significantly fluoxetine-treated animals, showed higher expression levels of syntaxin 1A. Antidepressants differentially affect expression levels of complexin I and more prominently complexin II and syntaxin 1A. The induction of complexin II and syntaxin 1A might strengthen the synaptic transmission at axo-dendritic or axo-axonal synapses. Previous post-mortem findings reporting on downregulation of complexins cannot be explained as mere effects of psychotropic drug treatment.